Komunikasi Interpersonal Keluarga sebagai Penunjang Kesehatan Mental Mahasiswa Rantau Asal Papua-Papua Barat - Hana Aviela Fedria Wowor; K. Y.S. Putri (PERSPEKTIF, 2021)
In this study, the researcher aims to find out how interpersonal communication in the family can support a person's mental health, especially overseas students. This study uses a qualitative method with a phenomenological approach, which focuses on telling the phenomenon of the role of family communication on student mentality, which is experienced directly by overseas students from Papua-West Papua. The results of this study show that communication plays a very important role in supporting one's mental health, especially overseas students who now have to study in a pandemic situation. Communication that supports this in the form of open communication and willing to listen. During this pandemic, some students chose to return to their hometowns, but some had to stay overseas due to certain conditions. Each student told a different experience, but more or less had something in common, namely feeling pressured or stressed with lectures. Through communication, students tend to feel their burden is reduced. Parental responses also build enthusiasm in students and provide strength, which reduces stress and helps students' mental health. The willingness of parents to hear stories and give positive words turned out to give students a feeling of comfort and relief.